Aaptamine Alters Vimentin Expression and Migration Capability of Triple-Negative Breast Cancer Cells - Khairani AF; Shalannandia WA; Bashari MH; Atik N (Journal of Experimental Pharmacology)
Astrid Feinisa Khairani,1,2,* Widad Aghnia Shalannandia,2,* Muhammad Hasan Bashari,1,2 Nur Atik1,2 1Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Sumedang, West Java, Indonesia; 2Graduate School of Master Program in Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Sumedang, West Java, Indonesia*These authors contributed equally to this workCorrespondence: Astrid Feinisa Khairani, Department of Biomedical Sciences, Faculty of Medicine, Universitas Padjadjaran, Jalan Raya Bandung – Sumedang Km 21, Jatinangor, Sumedang, West Java, 45363, Indonesia, Tel +62-22-7795594, Email astrid.khairani@unpad.ac.idPurpose: This study aimed to explore the effect of Aaptamine, an alkaloid derived from marine sponges, on the vimentin expression in both mRNA and protein levels and the migration capacity of breast cancer cells.Methods: The triple-negative breast cancer cell line MDA-MB-231 was used for in vitro experiments. Low-cytotoxicity concentrations of Aaptamine (12.5 to 50 μM) were given to MDA-MB-231 cells. The vimentin mRNA and protein expression were evaluated using RT-qPCR and immunofluorescence, respectively, 72 h after Aaptamine treatment. The migration scratch assay was conducted for 48 hours.Results: Aaptamine treatment in three different doses did not affect the expression of vimentin at the mRNA level while significantly lowering vimentin protein expression at the concentration of 12.5 μM. In addition, Aaptamine significantly inhibited breast cancer cell migration in a dose-dependent manner.Conclusion: Aaptamine inhibits vimentin protein expression and demonstrates anti-migration activity in the sub-cytotoxic dose.Keywords: aapatamine, cellular migration, EMT, MDA-MB-231, vimentin